Desain Sensor Suhu dan Kelengasan Tanah untuk Sistem Kendali Budidaya Tanaman Cabai (Capsicum annuum L.) - Sugeng Triyono; Mareli Telaumbanua; Yessi Mulyani; Titin Yulianti; Muhammad Amin; Agus Haryanto (agriTECH, 2018)
Cultivation crop is influenced by soil, water, climate, and crop properties. Air temperature is one of climate parameters which is considered for plant growing. Soil moisture represents soil and water factors and it generally plays an important role in crop cultivation. A crop requires soil moisture and air temperature for an optimum growth. a control system is proposed to create an optimum air temperature and soil moisture to support plant growth. The aim of this study was to design a precision measurement instrument, a control system that is able to control microclimate (air temperature and soil moisture) for optimal growth of chili (Capsicum annuum L.) crops. A design of environmental control was applied by using sensors for air temperature and soil moisture. Microcontrollers were connected to sensors with the water pump actuator and the irrigation pump through a relay module and a TIP122 transistor. The accuracy of DHT 22 temperature sensors and soil moisture sensors were calculated based on the approximate coefficient of determination, and the total errors of each sensor. The actuator performance in this design included the response rates and the duration of the working time. The performance tests were conducted 3 times without using chili plants. The coefficient of determination (R²) of temperature sensor 1, temperature sensor 2 and temperature sensor 3 were 0.999, 0.999, and 0.999, respectively. The total errors of the three sensors were -0.071 ºC, -0.085 ºC, and 0.014ºC, respectively. The coefficient of determination (R ²) of the soil moisture sensor 1, the soil moisture sensor 2, and the soil moisture sensor were 0.888, 0.8401, and 0.8963, respectively. The mean total errors for these three types of ranging sensors were -0.2204%, -0.0952% and -2.8049%, respectively.